Evaluation of Indoor Health and Comfort (IHC) in Classrooms: Quantitative Analysis of Lighting and Noise During the Afternoon Transition Period - Chillie Aurora Meydiano; Agil Fitri Handayani; Clara Devina Rizki Alfreda; Clarissya Ayuningtyas; Dafa Sashi Ramdhani; Tee Tze Kiong (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to evaluate Indoor Health and Comfort (IHC) in a classroom environment through a quantitative analysis of lighting (visual) and noise (auditory) parameters during the afternoon transition period (12:00–15:00 local time). A descriptive quantitative approach was employed using direct field measurements with a lux meter and a sound level meter in a 9 × 7 meter classroom. Measurements were conducted at 48 grid points with a spacing of 1 meter and at a height of approximately 0.8 meters, representing the students' working plane. The collected data were analyzed by comparing them with established standards, namely SNI 03-6575-2001 for lighting (≥250 Lux) and the Ministerial Decree on Environment No. 48 of 1996 for noise (≤55 dB). The results indicate that the average lighting level of 214.77 Lux is below the required standard, with approximately 62% of the measurement points classified as non-compliant. In contrast, the average noise level reaches 57.31 dB, exceeding the permissible threshold, with 72% of the points surpassing the limit. The simultaneous occurrence of insufficient lighting and excessive noise creates a double burden effect that may negatively influence students' visual comfort, concentration, and overall learning performance. Furthermore, temporal observations reveal a consistent decline in lighting intensity from approximately 242 Lux at 12:00 to 185 Lux at 15:00, confirming the afternoon transition period as a critical window for classroom IHC management. Therefore, this study recommends integrated improvement strategies, including optimizing artificial lighting systems, enhancing daylight utilization, and implementing acoustic control measures to improve classroom environmental quality